Calibration and adjustment of coherence scanning interferometry - Rahul Mandal (2015)
Coherence scanning interferometry (CSI) is a non-contacting optical technique which is widely used for the measurement of surface topography. CSI combines the lateral resolution of a high power microscope with the axial resolution of an interferometer. As with any other metrology instrument, CSI is calibrated to define measurement uncertainty. The traditional calibration procedure, as recommended by instrument manufacturers, consists of calibration of the axial and lateral scales of the instrument. Although calibration in this way provides uncertainties for the measurement of rectilinear artefacts, it does not give information about tilt-related uncertainty. If an object with varying slope is measured, significant errors are observed as the surface gradient increases. In this thesis a novel approach of calibration and adjustment for CSI using a spherical object is introduced. This new technique is based on three dimensional linear filtering theory. According to linear theory, smooth surface measurement in CSI can be represented as a linear filtering operation, where the filter is characterised either by point spread function (PSF) in space domain or by transfer function (TF) in spatial frequency domain. The derivation of these characteristics usually involves making the Born approximation, which is strictly only applicable for weakly scattering objects. However, for the case of surface scattering and making use of the Kirchhoff approximation, the system can be considered linear if multiple scattering is assumed to be negligible. In this case, the object is replaced by an infinitely thin foil-like object, which follows the surface topography and, therefore, is called the foil model of the surface. For an ideal aberration free instrument, the linear characteristics are determined by the numerical aperture of the objective lens and the bandwidth of the source. However, it is found that the PSF and TF of a commercial instrument can depart significantly from theory and result in a significant measurement error. A new method, based on modified inverse filter to compensate the phase and amplitude-related errors in the system PSF/TF, is demonstrated. Finally, a method based on de-warping to compensate distortion is discussed. The application of the linear theory as well as modified inverse filter is dependent on the assumption of the shift invariance. As distortion introduces a field dependent magnification, the presence of distortion for CSI with relatively large field of view, restricts the applicability of the linear theory. Along with this restriction, distortion also introduces erroneous height measurement for objects with gradients. This new approach, based on de-warping, resolves the problems associated with distortion.